Major trials in coronary intervention from 2018. (July 2019) - Patel, Amit; Marah, Naddi; Balan, Prakash
Abstract : Purpose of review: This article will review the major clinical trials related to coronary intervention that were released in 2018. Areas of interest include lesion assessment, novel stent design, acute coronary syndromes (ACSs), and major breakthroughs in chronic total occlusion interventions. Recent findings: The benefit of intracoronary imaging and hemodynamic assessment was demonstrated by multiple studies, which found improved procedural and clinical outcomes in patients who underwent advanced assessment of intracoronary lesions. The optimal use of drug-coated balloons in coronary disease still remains unclear with conflicting data regarding the benefit of DCB over everolimus-eluting stents for the treatment of in-stent restenosis. Trials in bioresorbable scaffolds also saw a high level of interest after the ABSORB IV trial showed promising results with changes in implantation technique. Multiple studies evaluated complete revascularization versus infarct-related only revascularization in patients with ACS; however, data was conflicting in regard to what is the best strategy. Lastly, the EUROCTO study was released in 2018 and was the first trial to show symptomatic benefit of revascularization of chronic total occlusions. Summary: The ESC/EACTS guidelines on complete versus partial revascularization, treatment of in-stent restenosis, and revascularization during cardiogenic shock were updated to reflect data obtained from trials released in 2018.